Suggestion of Raspailia (Hymeraphiopsis) septentrionalis as replacement name for Raspailia (Hymeraphiopsis) fruticosa Lehnert & Stone, 2015 - Lehnert, Helmut; Stone, Robert P. (Zootaxa, 2016)
Shortly after publication of Raspailia (Hymeraphiopsis) fruticosa Lehnert & Stone, 2015 Rob Van Soest (pers. communication) noticed that this species name is a junior primary homonym of Raspailia fruticosa Dendy, 1887, now accepted as Endectyon fruticosa. According to the ICZN the published species name is unavailable and we now suggest to replace the name with Raspailia (Hymeraphiopsis) septentrionalis (holotype deposited at the Zoologische Staatssammlung München, ZSM 20150392, collection data published in Lehnert & Stone 2015).